DIGITAL LIBRARY AS STRATEGIES TO IMPROVE DIGITAL ISLAMIC LITERACY FOR EDUCATION - Maslamah (jfpublisher, 2023)
National Literacy Movement (GLN) become the main focus of the Government. Digital library is a strategic alternative to improve community literacy skills and become the Government's primary focus. Digital library is a strategic alternative to improve community literacy skills. This research aims to examine the strategy to improve digital Islamic literacy for the benefit of education through a digital library, one of which is to build digital literacy in a mosque. Literacy movement in mosques is a synergistic step as an effort to increase knowledge and insight also deradicalization. Through this research activity, UIN Raden Mas Said Surakarta implements as a digital library for worshipers at Al Fauziyah Mosque, Sukoharjo because it has the advantage of saving space. has multiple access, is not limited by space and time, and costs less. It has multiple access, is not limited by space and time, and costs less. The congregation's response to the ease of learning digital library has the total of 88,42%, the ease of understanding screen display is 87.37%, the ease of finding books 85,26%, the ease to access book is 87,37% and the usefulness of the digital library for the congregation is 95,79%. The accessibility variable with digital library usefulness variable has a very strong correlation